2020
DOI: 10.1177/0300060520974249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transmitted glow point at a priori chosen depth (1 cm below vocal cords) for lightwand intubation: a prospective observational study

Abstract: Objective When performing lightwand intubation, an improper transmitted glow position before tube advancement can cause intubation failure or laryngeal injury. This study was performed to explore the transmitted glow point corresponding to a priori chosen depth for lightwand intubation. Methods Before lightwand intubation, we marked the transmitted glow point from a bronchoscope on the neck when it reached 1 cm below the vocal cords. Lightwand intubation was then performed using this marking point. The distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In our study, we stopped at the brightest point during lightwand insertion. Cho et al reported that 1 cm below the vocal cords was an effective glow point for the lightwand tip to avoid deep or shallow insertions (21). They showed a 93.5% success rate at the first attempt, which was similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we stopped at the brightest point during lightwand insertion. Cho et al reported that 1 cm below the vocal cords was an effective glow point for the lightwand tip to avoid deep or shallow insertions (21). They showed a 93.5% success rate at the first attempt, which was similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…[12] However, the use of video laryngoscopy may be limited in patients with restricted opening and cervical ankylosis. [13] Tracheal intubation using a lightwand is a good alternative for patients with restricted opening and cervical ankylosis. Therefore, in this case, we chose to use a lightwand-guided tracheal intubation that is easy to perform and does not require exposure of the vocal cords.…”
Section: Discussionmentioning
confidence: 99%